Endothelial injury in rheumatoid arthritis: a crosstalk between dimethylarginines and systemic inflammation. Issue 1 (December 2017) - Dimitroulas, Theodoros; Hodson, James; Sandoo, Aamer; Smith, Jacqueline; Kitas, George
Abstract Background Symmetric (SDMA) and asymmetric (ADMA) dimethylarginines have emerged as novel biomarkers of cardiovascular disease (CVD) in several disease settings associated with atherosclerosis. Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease characterized by high CVD mortality and morbidity. ADMA and SDMA levels are abnormal in RA patients, but their correlation with assessments of endothelial function and structure remains unknown. We aimed to investigate whether SDMA and ADMA are associated with carotid intima media thickness (cIMT) and arterial stiffness as well as non-invasive assessments of in vivo micro- and macrovascular endothelial function in RA patients with high systemic inflammatory load. Method ADMA and SDMA levels were measured using immunoassays in 197 RA individuals. Twenty-six of these [23 (86.4%) females, median age 70, quartiles (60, 73)] were identified as having high inflammatory markers [erythrocyte sedimentation rate (ESR) >25 mm/hr and C-reactive protein (CRP) > 5 mg/L], and were compared to the remainder of the cohort. Patients underwent assessments of microvascular endothelium-dependent and endothelium-independent function [laser Doppler imaging with iontophoresis of acetylcholine (Ach) and sodium-nitroprusside (SNP) respectively], macrovascular endothelium-dependent and endothelium-independent function (flow-mediated dilatation and glyceryl-trinitrate-mediated dilation respectively), and vascular morphology [pulse wave analysis, and carotid intima media thickness (cIMT)]. Results Significant interactions with inflammation were detected in the associations between ACh and both SDMA (p = 0.014) and ADMA:SDMA ratio (p = 0.027), as well as between SNP and SDMA (p = 0.042) and between arterial stiffness and ADMA:SDMA (p = 0.036), with the associations being stronger in the patients with high inflammatory markers in each case. Conclusions Besides their emerging role as markers of endothelial dysfunction SDMA and ADMA may promote endothelial injury in RA as mediators of the adverse effects of systemic inflammation on micro- and macrovasculature respectively in patients with active disease.